Sport Karate and the Pursuit of Wellness: A Participant Observation Study of a dojo in Scotland - Turelli, Fabiana Cristina; Tejero-González, Carlos María; Vaz, Alexandre Fernandez; Kirk, David (Frontiers in Sociology, 2020)
Health problems in society are numerous, not least stress and stress-related illness. Physical activities, including martial arts, are increasingly viewed as a means of managing such risks to health. While there are forms of karate that have a philosophical and meditative character that is related to spiritual wellness, karate as a competitive sport is less likely to be thought of in this light. The purpose of this paper is to present through a participant observation study the representations that karateka of the dojo, make of sportive karate as a resource to achieve wellness. Drawing on an eight months’ immersion in the dojo, we identify five themes that express these karateka’s views of sport karate and wellness, the importance of fitness, beauty in punches and kicks, how to embrace fear, the aggressive attitude as a posture in life, and the superiority given by control. The findings lead us to reflect on the need for further research to see if they are repeated in other martial arts, and if many more groups find wellness as a primary motivation for their participation.